2019
DOI: 10.3390/ejihpe10010019
|View full text |Cite
|
Sign up to set email alerts
|

“Food is Environmentally and Culturally Specific!”: A Preliminary Qualitative Study on U.S. Immigrant Parents’ Perceptions of School Lunch

Abstract: Children spend most of their day hours in school, so the dietary choices they make during school days are important for their childhood development and later life. This research examined food choices among immigrant families with school-age children in Indiana, USA. Open-ended questions were answered by 52 immigrant parents in 2017. Parents who answered the questions had children in classes ranging from kindergarten to grade 12. NVivo 11 was used for the initial analysis of the dataset, and several themes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… 21 Similarly, a study evaluating perceptions of school lunches among US immigrant parents found that the convenience of school lunches enabled them to have more time for other important chores at home, and free school meals enabled them to save money for other necessities. 30 Our study finds that the perceived benefits of school meals are similar across racial and ethnic groups, thus highlighting the universal feeling of meal support under a UFSM program.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“… 21 Similarly, a study evaluating perceptions of school lunches among US immigrant parents found that the convenience of school lunches enabled them to have more time for other important chores at home, and free school meals enabled them to save money for other necessities. 30 Our study finds that the perceived benefits of school meals are similar across racial and ethnic groups, thus highlighting the universal feeling of meal support under a UFSM program.…”
Section: Discussionmentioning
confidence: 53%
“…Multiple factors could explain these differences, including cultural food norms that favor more fresh whole foods, schools' inability to offer adequate diversity of foods that meet students' racial and ethnic backgrounds, dietary restrictions due to medical needs, differences in the perceptions of immigrant parents about American foods, and disparities in the school food environment, among others. 13 , 30 , 31 , 55 , 56 Prior studies have reported that school meals do not include enough culturally appropriate foods. 30 , 31 One study assessing school breakfast perceptions among diverse immigrant families found that, when schools did not offer enough culturally appropriate hot foods, students were less likely to participate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also saw no significant associations between other acculturation variables and school meal participation, thus suggesting that school meal participation may not be influenced by acculturation the same way other obesogenic behaviors are. [28][29][30][31][32][33][34][35][36] In a qualitative study done within immigrant parents, participants explained that their children often do not want to bring foods from home so they could be seen as ''mainstream'' and avoiding having their food ''made fun of'' 37 This may explain why there were little differences between school meal participation and acculturation variables.…”
Section: Discussionmentioning
confidence: 99%
“…Given that immigrants to the US are known to face challenges in their dietary habits on their arrival to the country, and the fact that these are linked to obesity and chronic disease, a research team in Indiana recently examined food choices among immigrant families with school-age children. 4 The 52 parents who took part in the study had children in classes ranging from kindergarten to grade 12. They felt that schools were generally serving the needs of immigrant children by serving varieties of foods during lunchtime.…”
mentioning
confidence: 99%